Peran mediasi keunggulan kompetitif pada faktor determinan kinerja bisnis UKM di sentra tenun batik di Jawa Tengah - Asyhari Asyhari; Sri Hindah Pudjihastuti; Dian Marhaeni Kurdaningsih (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2018)
Industry era 4.0 poses challenges for Small and Medium Enterprises (SMEs) to expand their business into the global market, but there are still many obstacles related to the readiness of resources and technology. This study aims to analyze the influence of business strategy quality, seller behavior ethics, process innovation, entrepreneurship orientation perspective, and business environment adaptability to the business performance of SMEs, with the role of mediation of competitive advantage. This study is a quantitative inferential research with primary data sources through questionnaires. The sample that used in this study is 80 SMEs entrepreneurs of batik center in Central Java, who taken uses purposive sampling method. The data are analyzed using Partial Least Square Structural Equation Model (PLS-SEM) with SmartPLS software. The results of the first study show that the quality of business strategy and behavioral ethics of the seller partially positive effect on competitive advantage. The second finding of this study shows the quality of business strategy, seller behavior ethic, process innovation, entrepreneurship orientation perspective, business environment adaptability, and partial competitive advantage positively affect business performance. The results of this study are expected to be useful in theoretical development, especially strategic management.